A study of the ground-attachment process in natural lightning with emphasis on its breakthrough phase. Issue 1 (December 2017) - Tran, M.; Rakov, V.
Abstract Synchronized high-speed (124 or 210 kiloframes per second) video images and wideband electromagnetic field records of the attachment process were obtained for 4 negative strokes in natural lightning at the Lightning Observatory in Gainesville, Florida. The majority of imaged upward connecting leaders (UCLs) and upward unconnected leaders, inferred to be mostly initiated from trees, exhibited a pulsating behavior (brightening/fading cycles). UCLs, whose maximum extent ranged from 11 to 25 m, propagated in virgin air at speeds ranging from 1.8 × 105 to 6.0 × 105  m/s with a mean of 3.4 × 105  m/s. Within about 100 m of the ground, the ratio of speeds of the downward negative leader and the corresponding positive UCL was about 3–4 for 2 events and 0.5 for 1 event. The breakthrough phase (final jump) was imaged for 2 events. The initial length of the common streamer zone (CSZ) was estimated to be about 30–40 m. For 2 events, speeds of positive and negative leaders developing toward each other inside the CSZ were found to be between 2.4 × 106 and 3.7 × 106  m/s. For 1 event, opposite polarity leaders were observed to accelerate inside the CSZ. The current at the end of the breakthrough phase, lasting on average 4.7 μs, was estimated to be approximately one-half of the overall current peak. Thus, about one-half of the current peak traditionally attributed to the return-stroke process is actually associated with two leaders extending toward each other to collision inside the CSZ.